Comportamentos de crianças do espectro do autismo com seus pares no contexto de educação musical - NASCIMENTO, Paulyane Silva do (2016)
The Autism Spectrum Disorder (ASD) is characterized by impairments in the areas of social interaction, communication, behavior and sensory processing. Aspects related to difficulties in social interaction repertoire, as well as strategies to help them behave more adequately have been widely studied. Among these strategies, those using music have received attention. The present study aims to investigate the benefits of music education to the social interaction of children with ASD, with their peers, focusing on both the quality and frequency of these behaviors. Two ASD children, aged 5 and 6 years respectively, who attended a percussion class group, participated in the study. The Demographics and Development information enabled the children´s profiles to be drawn. The social interaction behaviors were coded using a Behavioral Observation Protocol during 8 sessions (240 minutes). The results suggest that both tended to increase initiatives and spontaneous responses and to decrease non-functional behaviors as the sessions progressed. It was found that stereotypies were used by the ASD children when attempting to interact with others, albeit sporadically. The role of context, of the children's profile and of adult behavioral management of children in promoting interactions was highlighted.